Introducing Workers’ Embedded Agency: Insights from the Brazilian Subsidiaries of a Multinational Corporation - Frangi, Lorenzo (Relations industrielles / Industrial Relations, 2014)
SummaryThe relevance of subsidiary embeddedness in a macro-institutional environment can in no way overshadow the importance of the micro-political agency of social actors. While some researchers focus on local management’s “embedded agency,” we focus on a less-developed aspect: workers’ “embedded agency.” In order to do so, we propose an analytical model that is based on the Varieties of Capitalism model and its subsequent developments, but that also includes the workers as an active agent. This model allows us to observe the institutional resources that workers can actively mobilize. We specifically focus on the characteristics of industrial relations and education institutional sub-systems. We apply the developed analytical model to the case of the Brazilian subsidiaries of a highly global multinational corporation (MNC). Brazil represents a context where institutional constraints (i.e. corporatist industrial relations and a dualist education system) make workers’ actions the least favorable. Moreover, the highly integrated organizational environment of the MNC further reinforces this aspect. In turn, this makes it more compelling to discover how workers can nevertheless strategically activate some resources to improve their conditions. We conduct a case study and collect empirical data through semi-structured interviews and documentary analysis. More specifically, we discuss three examples of workers’ “embedded agency” (i.e. election of a bilateral committee for the prevention of accidents; plant closure; and internship and training). These bring analytical attention to workers’ collective and individual actions as well as intra- and extra-subsidiary mobilization of institutional resources.